The level of scientific literacy and its relation with a making decision Field study of the third secondary scientific students in the secretariat، Sana'a - Al-Homaidi, Hazza Abdu; Al-Dagashi, Abdu Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to recognize the level of scientific literacy and its relation with making decisions of the third secondary scientific students in the secretariat (Sana'a).-The study used the descriptive statistics methodology that is regarded as a good methodology to this study.The study came up with the following conclusion:• A low – level of the scientific literacy of the study sample on the scientific literacy in general as well as its subsidiary axis than the extreme that the study pointed which is (80%).• There were statically differences at the level (0.05)in the favorite of male students in general exam،and there are no statically differences in the scientific knowledge.• Three were statically differences at the level (0.05) in the favorite of male students in the public schools. However، there were no statically differences in (science nature –scientific knowledge –STS)• No statically differences at the level (0.05) in the average marks of the private schools students in general exam and its subsidiary axis.• No statically differences were found at the level (0.05) between the averages of students' marks in general and (science nature، scientific knowledge) of both the public and private schools، but there were in the (STS) the favorite of private schools.• There were a positive relation (R=0.40) at the level (0.01) between the level of decision making and the scientific literacy together with (science nature، scientific knowledge، STS) R= (0.37-0.39-0.31) respectively.Recommendations: The decision making and level of scientific literacy should be raised among the third secondary science students، and it is necessary to give a list of scientific literacy، to have training sessions to science teachers، in order to renew their information، increase their scientific literacy and their decision making.
Keywords: scientific literacy; science nature; scientific knowledge; STS; decision making; Sanaa; Capital Municipality